PELATIHAN PENGENALAN CODING BAGI GURU SD MENGGUNAKAN SCRATCH Jr - Andik Adi Suryanto; Amaludin Arifia; Alfian Nurlifa; Asfan Muqtadir; Fitroh Amaluddin; Andy Haryoko; Aris Wijayanti (Universitas Methodist Indonesia, 2022)
Coding is an instruction written using a particular programming language. Coding is currently the most important part of developing technology and applications in today's digital era. In this independent curriculum students are expected to be able to think critically and be able to solve the problems they face and have intellectual intelligence. Scratch Jr. is an application used for basic coding learning for ages 5-7 years. With coding can develop intellectual intelligence in thinking logically in solving problems.